Use of Activated Carbon from Vegetable Residual Biomass with SiO2 Nanoparticles for the Removal of Organic Compounds in Wastewater from the Hydrocarbon Sector - Adan Leon-Bermudez; Michell A. Jimenez-Caballero; Sergio F. Castellanos-Amador; Dario Pena-Ballesteros; Miller H. Salas-Rondon (Chemical Engineering Transactions)
Colombia has significant potential for the cultivation of cocoa, coffee, and oil palm. However, activities also generate substantial amounts of vegetable residual biomass. For this reason, various industrial sectors have shown interest in utilizing vegetable residual biomass to promote environmental sustainability. In this research, activated carbons were prepared from vegetable residual biomass combined with SiO2 nanoparticles for the removal of representative organic compounds in founds in produced water from the hydrocarbons industry. The organic compounds selected as model species for the development of this research were methylene blue (MB), phenol (Ph), and sodium dodecylbenzenesulfonate (SDBS). The activated carbons from residual vegetable biomass of cocoa, coffee, and oil palm kernel were prepared in a tubular furnace using the thermochemical process with a phosphoric acid-to-biomass impregnation ratio of 1:1, under reaction conditions of 430 °C for 30 minutes. The impregnation treatment of the activated carbons was performed using the coprecipitation method at the laboratory scale, employing ethanol solutions with 5,400 mg/L of SiO2 nanoparticles. From the Scanning Electron Microscopy / Energy Dispersive Spectroscopy (SEM-EDS) analysis, it was determined that the new adsorbent materials contain channels that facilitate the impregnation of SiO2 nanoparticles. Textural tests showed that the prepared carbons exhibited surface areas in the range of 600 to 1200 m²/g. The removals of methylene blue (MB), phenol (Ph), and sodium dodecyl benzene sulfonate (SDBS) were 93.85%, 97.09% and 98.15% by weight, respectively. However, the addition of SiO2 nanoparticles increased both the surface area and the percentage of removal of the organic compounds. The adsorption results were fitted to adsorption isotherms, and according to the correlation coefficient R², the isotherms were classified in ascending order with the Freundlich>Langmuir>Temkin models. The methodology proposed in this study demonstrates that the activated carbon/SiO2 nanoparticles are suitable for removing organic compounds present in wastewater.